Documentary time : film and phenomenology - Malin Wahlberg (University of Minnesota Press, 2008)
This book aims at a reassessment of image and time from the perspective of documentary film. The aesthetic and affective dimensions of documentary film were once highly disregarded in a scholarly field traditionally dominated by discourses on social representation and the rhetoric incentive of nonfiction cinema. Hopefully, the discussions that follow will add to recent work on film and media, which has convincingly shown that aesthetic and psychological aspects of cinema are indeed issues relevant for studying documentary film. Documentary aesthetics has been the subject of several panels at the Visible Evidence conference, which in many ways inspired the writing of this book. In classical film theory the varied expressions of documentary film have often been marginalized or overlooked. If the aesthetic and formal experimentation of documentary film calls for further research, aspects of temporality in these nonfictitious genres represent an even more significant lacuna. Not even Gilles Deleuze recognized the complex relation between the time of the image, allegories of time, and time experience in documentary.4 This is remarkable given that his idea of cinema as the mnemonic machine par excellence has much in common with the sublime representations of time, history, and memory offered by documentary. Although documentary examples have been rare in the classical context of film aesthetics, important reflections have been made regarding the material and existential signification of cinema and temporality. Looking back at this long-standing debate and the related issues of television, video, and digital culture, it is striking to note how the problem of image and time has always oscillated between ontological claims about the specific medium and the experience of moving images. The phenomenological tradition in film theory demands recognition in this respect. A critical mapping of this philosophical inheritance may be helpful in contextualizing some persistent themes on time experience in film that remain salient in the contemporary culture of moving images. Aside from a contextualization of the phenomenology of image and time, the discussion in this book aims at a deepened account of the promises and pitfalls of a phenomenological perspective in film studies and, more specifically, aims to reconsider some phenomenological issues that may advance our current understanding of documentary film and video. I cannot aspire to exhaustive answers to the overall methodological problems addressed or touched upon here, although it has been my ambition to grapple with these concerns on both a metatheoretical and a practical level. The title of this book demands clarification, and I will begin by demarcating the French context of existential phenomenology, the philosophical tradition of primary interest for the following discussion.